EFFECT OF LIGNOCAINE ADDITION ON THE PROPERTIES OF IRREVERSIBLE HYDROCOLLOID IMPRESSION MATERIAL - Qaisar, Aneela; Hussain, Shafqat; Yazdanie, Nazia; Khalid, Hina; Khan, Abdul Samad (Journal of Ayub Medical College Abbottabad, 2019)
Background: Irreversible hydrocolloid impression materials have been a staple in dentistry and useful for the fabrication of dental prosthesis. Gagging is most commonly experienced during maxillary impression making, which may affect the clinical management of the patient. Different techniques have been described to alleviate this problem. One of them is mixing lignocaine local anesthetic solution in irreversible hydrocolloid impression material before making the impression. The objective of this study was to evaluate the effect of lignocaine addition in irreversible hydrocolloid impression on the properties of irreversible hydrocolloid impression materials. Methods: Irreversible hydrocolloid was mixed with water (Control group) or water and adrenalin (Lidocaine hydrochloride) (Experimental group). Compressive strength, tear strength and setting time were measured according to ISO1567 and ANSI/ADA specifications 18. The structural analysis of both groups was also evaluated by Fourier Transform Infrared Spectroscopy (FTIR). Results: In the experimental group, insignificant decrease was observed in compressive and tear strength of irreversible hydrocolloid (p >0.05). There was significant (p <0.05) increase in setting time of irreversible hydrocolloid impression material. FTIR analysis indicated no change in chemistry of irreversible hydrocolloid before and after setting. Conclusion: Addition of lignocaine in irreversible hydrocolloid impression material may result in control of gag reflex without affecting its mechanical and chemical properties. Keywords: Irreversible Hydrocolloid; lignocaine; Gag reflex; dental prosthesis; FTIR